2020
DOI: 10.1186/s12889-020-09701-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of knowledge, risk perceptions, and cues to action among Iranian women concerning cervical cancer and screening: a qualitative exploration

Abstract: Background Iran has a low incidence but higher rate of death from cervical cancer (CC). The country is in the process of implementing an organized screening program including HPV testing and cytology. Studies show high dropout in continued testing among eligible women. This qualitative study aimed to explore women’s awareness regarding CC and CC testing and the role of knowledge, perceived risk, and cues to action in this process. Method … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…This is consistent with a study in Kenya in 2014 [ 31 ]. Similarly other studies revealed that physician advice for cervical cancer screening [ 40 ], someone they knew screened before, information from mass media and educational talks were important cues for women to attend the screening test [ 41 ]. This finding implies the need to consider important cues to take action in cervical cancer screening programs to improve the screening uptake by women.…”
Section: Discussionmentioning
confidence: 93%
“…This is consistent with a study in Kenya in 2014 [ 31 ]. Similarly other studies revealed that physician advice for cervical cancer screening [ 40 ], someone they knew screened before, information from mass media and educational talks were important cues for women to attend the screening test [ 41 ]. This finding implies the need to consider important cues to take action in cervical cancer screening programs to improve the screening uptake by women.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, most women would agree to their daughters receiving the HPV vaccine for free or at a cost to themselves. Availability and uptake of the HPV vaccine could play a crucial role in the prevention and reduction of morbidity and mortality of CC [41,42]. This study assessed the Palestinian women's awareness level of HPV in addition to its vaccine and examined the acceptability of the HPV vaccine to provide baseline information for the implementation of future awareness campaigns and to facilitate the launch of HPV immunization programs.…”
Section: Discussionmentioning
confidence: 99%
“…Effective implementation of HPV vaccination programs is considered one of the cornerstones to reducing the burden of CC, particularly in low-and middle-income countries [14,[41][42][43]. For a vaccination program to be effective, both awareness of its benefits and availability are important to ensure wide uptake among the population [43].…”
Section: Good Awareness Of Hpv and Its Vaccine And The Associated Fac...mentioning
confidence: 99%
“…The addressing of both cervical cancer risk factors and protective factors, as well as content about myths and stigmas of the disease, are mandatory for better engagement of women in health-educational strategies focusing on self-care practices related to cervical cancer prevention (Cooper et al, 2020;Taghizadeh et al, 2020;Sitaresmi et al, 2020). It seems that guaranteeing only informative content on Instagram underestimates the potential of this social network as a driver of behavioral changes based on improving knowledge about self-care in health.…”
Section: Social Interaction Analysismentioning
confidence: 99%